2022
DOI: 10.25159/2663-5895/12229
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Pre-service Teachers’ Acceptance of Online Learning to Promote Social Distancing

Abstract: The outbreak of the novel Coronavirus disease (COVID-19), which was declared a global pandemic on 11 March 2020, has upended the world. To combat its spread, social distancing was adopted as recommended by health professionals and the higher education institutions (HEIs) were not spared. Despite the continuation of the academic agenda, social distancing forced lecturers and their students apart. As a result, the goal of this study was to examine factors that influence pre-service teachers’ acceptance of online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Motivation and engagement are influenced by attitudes and preparedness. Düzgün and Kaşkaya (2023) report that pre-service teachers' views of online instruction were more positive in certain programs, such as social studies and early childhood education, than in others, while Chibisa et al (2022) found that pre-service teachers' perceptions of the usage of online learning influenced their readiness to adopt it, concluding that for online learning to be implemented successfully, pre-service teachers' attitudes must change. According to Atmaca (2023), the effectiveness of online education could be improved by raising the caliber of online learning platforms and the instruction given to pre-service teachers and their educators.…”
Section: Engagement Motivation Skill Development and Satisfaction In ...mentioning
confidence: 99%
“…Motivation and engagement are influenced by attitudes and preparedness. Düzgün and Kaşkaya (2023) report that pre-service teachers' views of online instruction were more positive in certain programs, such as social studies and early childhood education, than in others, while Chibisa et al (2022) found that pre-service teachers' perceptions of the usage of online learning influenced their readiness to adopt it, concluding that for online learning to be implemented successfully, pre-service teachers' attitudes must change. According to Atmaca (2023), the effectiveness of online education could be improved by raising the caliber of online learning platforms and the instruction given to pre-service teachers and their educators.…”
Section: Engagement Motivation Skill Development and Satisfaction In ...mentioning
confidence: 99%